Technical brief. Programming review of visual Basic.NET for the laboratory automation industry. - Harkness R; Crook M; Povery D (JALA: Journal of the Association for Laboratory Automation, 2007)
The latest version of Microsoft Visual Basic (2005) is built upon the Microsoft .NET Framework. It has finally become a fully-fledged Object Oriented Language with all the associated features one would come to expect. It allows Visual Basic programmers to tackle much larger applications, through improved scalability and reusability. This article discusses the new features using code examples to real applications in the Laboratory Automation environment.